“Conservation” et “coexistence” en primatologie : antagonismes et recoupements - Vincent Leblan; Papa Ibnou Ndiaye; Victor Narat (Revue de Primatologie)
This introduction to the thematic section “Conservation” and “Coexistence” in Primatology: Antagonisms and Overlaps examines the semantic and political intersection and opposition of these two key notions when it comes to addressing the relationships of humans and other primates. Taking into account the gradation of coexistence situations illustrated by the articles of this thematic section, we consider that the degree of openness of primatological research sites, from the fully protected area to the shared landscape, corresponds to values that are rarely made explicit by the researchers themselves. We suggest that adherence to these values of closure or openness are as much a matter of generation as of a founding field experience in our scientific careers. We consider that the political-economic issues specific to each research site or region durably shape our political visions of conservation and coexistence. On the one hand, we illustrate this principle on the basis of the diversity of positions and values expressed in primatology regarding chimpanzee conservation in West Africa. On the other hand, we examine how power relations within this research community may influence the global conservation policies of West African chimpanzees towards more or less coexistence with humans. This thematic section reflects the "societal choices" implied by each way of engaging in conservation in primatology that are rarely made explicit.